Development and validation of a novel method "SpermX™" for high throughput differential extraction processing of sexual assault kits (SAKs) for DNA analysis. (July 2022) - Sinha, Sudhir K.; Brown, Hiromi; Holt, Hailey; Khan, Mah-ro; Brown, Ryan; Sgueglia, Joanne B.; Loftus, Andrew; Murphy, Gina; Montgomery, Anne
Abstract: The Sperm X method uses a nanotechnology derived polymer membrane that functions as a separation medium to effectively trap sperm cells while enabling efficient flow through of the digested epithelial cell DNA. This specialized membrane enabled development of a method that could significantly increase a forensic laboratory's ability to obtain male sperm fraction DNA profiles. The SpermX device provides a rapid, reproducible procedure that is easy to implement in a single-tube format as well as high-throughput truly automated hands-free workflows. Validation studies, performed using the manual SpermX method, include sensitivity, stability, precision (reproducibility and repeatability), mixtures, and a method comparison to the traditional differential extraction. Sensitivity and method comparison studies demonstrated a wide range of sperm cells, from a high of over 2.78 million cells (9158 ng) to a low of 25 cells (83 pg), can be trapped by the SpermX membrane. Stability studies on various substrates (i.e., carpet, cotton, denim, polyester, and silk) and degraded semen gave the expected male DNA profiles. Data from the same operator and a different operator were consistent with low variance. Mixtures, with ratios ranging from approximately 10:1–18182:1, created to simulate real casework type samples including buccal/semen, vaginal epithelial/semen, and post coital swabs at different time intervals, were tested. A comparison of the SpermX method to the conventional differential extraction method resulted in comparable probative male profile allelic data and associated statistical probabilities. For low level sperm samples, down to 25 sperm cells (83 pg), the SpermX method outperformed the conventional differential extraction with more genotypic information and associated probabilities. Highlights: New method described for forensic differential extraction. The method, SpermX™, is based on a nanotechnology derived polymer membrane. SpermX™ is amenable to high-throughput automated hands-free workflows. SpermX™ developmental validation studies are described.